Pemanfaatan Teknologi Informasi dan Komunikasi untuk Lansia di Indonesia: Sebuah Studi Literatur - Ismail, Naufaludin (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
Study of the role of Information and Communication Technology (ICT) in supporting the inclusiveness of the elderly is becoming important as the number of elderly people in Indonesia increases. The global elderly population is increasing, including in Indonesia. Data shows that the percentage of the elderly population has doubled in the last five decades. Literature research in the last ten years highlights various uses of ICT to support the lives of the elderly, including application development and hardware implementation such as the Internet of Things (IoT) and Smart Home. Apart from that, the potential of future technologies such as Virtual Reality (VR) was also discussed. The research method used is a qualitative approach with literature study and descriptive analysis. Counseling on the use of ICT, developing elderly-friendly applications, and implementing integrated information systems were identified as initiatives that increase the inclusivity of elderly people in the digital era. A study of literature in scientific journals over the last 10 years shows that the use of ICT, including software, hardware and VR, has expanded
Keywords: Elderly; Communication; Inclusion; Information and Communication Technology